2020
DOI: 10.3390/pr8111410
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Potential Induced by Ambient Particulate Matters with Acellular Assays: A Review

Abstract: Acellular assays of oxidative potential (OP) induced by ambient particulate matters (PMs) are of great significance in screening for toxicity in PMs. In this review, several typical OP measurement techniques, including the respiratory tract lining fluid assay (RTLF), ascorbate depletion assay (AA), dithiothreitol assay (DTT), chemiluminescent reductive acridinium triggering (CRAT), dichlorofluorescin assay (DCFH) and electron paramagnetic/spin resonance assay (EPR/ESR) are discussed and their sensitivity to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 94 publications
(176 reference statements)
0
26
0
Order By: Relevance
“…Although the specific mechanisms of PM-induced health effects are still largely unknown, there is increasing consensus that they involve oxidative stress through the generation of excessive reactive oxygen species (ROS) and/or inadequate antioxidant defenses [4][5][6][7][8][9][10]. Thus, the oxidative potential, representing the capacity of PM to oxidize molecules generating ROS, has been suggested as a representative metric of PM toxicity related to oxidative stress [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the specific mechanisms of PM-induced health effects are still largely unknown, there is increasing consensus that they involve oxidative stress through the generation of excessive reactive oxygen species (ROS) and/or inadequate antioxidant defenses [4][5][6][7][8][9][10]. Thus, the oxidative potential, representing the capacity of PM to oxidize molecules generating ROS, has been suggested as a representative metric of PM toxicity related to oxidative stress [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…PMs are composed of carbon cores and several soluble and insoluble components including acids, organic chemicals, metals, endotoxins, pollen, and fungal debris on their surface [ 34 ]. Therefore, the underlying mechanisms by which PM exerts its biological effects are complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, the respiratory aerosol is different from an ambient aerosol defined in atmospheric science where it generally refers to the suspension system of solid particles, liquid particles, or both of them in a gaseous medium ( Tang et al, 2006 , Freney et al, 2010 ). Ambient aerosol is considered potentially harmful to human health as it can contain not only hazardous elements and chemicals ( Shao et al, 2017 , Feng et al, 2020 , Rao et al, 2020 ), but also pathogens such as bacteria, fungi, and viruses ( Han et al, 2021 ). Airborne fine particles (PM 2.5 ) are considered of greater health significance with their large surface area and strong adsorption capability ( Ding and Zhu, 2003 , Shao et al, 2018 ).…”
Section: Overview Of Possible Transmission Pathwaysmentioning
confidence: 99%
“…Studies have shown that the high infection rate of COVID-19 is related to poor air quality ( Cazzolla Gatti et al, 2020 , Coccia, 2020 , Conticini et al, 2020 ). Air pollution can cause inflammations, cell damage, and respiratory diseases ( Shao et al, 2017 , Feng et al, 2020 , Rao et al, 2020 , Wang et al, 2021 ). High concentrations of volatile organic compounds (VOCs) can cause health risks ( Yan et al, 2015 ).…”
Section: Overview Of Possible Transmission Pathwaysmentioning
confidence: 99%